2006
DOI: 10.1073/pnas.0601473103
|View full text |Cite
|
Sign up to set email alerts
|

Running over rough terrain reveals limb control for intrinsic stability

Abstract: Legged animals routinely negotiate rough, unpredictable terrain with agility and stability that outmatches any human-built machine. Yet, we know surprisingly little about how animals accomplish this. Current knowledge is largely limited to studies of steady movement. These studies have revealed fundamental mechanisms used by terrestrial animals for steady locomotion. However, it is unclear whether these models provide an appropriate framework for the neuromuscular and mechanical strategies used to achieve dyna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
228
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 190 publications
(239 citation statements)
references
References 40 publications
11
228
0
Order By: Relevance
“…Indeed, our statistical analyses revealed few parameters that discriminate between footfall orders. Those parameters include relative limb length as well as relative limb protraction and retraction -parameters that play a predominant role in self-stability during perturbed locomotion in bipeds (Geyer et al, 2005;Daley and Biewener, 2006;Seyfarth et al, 2002). We therefore suggest that these parameters play an overall important role during terrestrial locomotion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, our statistical analyses revealed few parameters that discriminate between footfall orders. Those parameters include relative limb length as well as relative limb protraction and retraction -parameters that play a predominant role in self-stability during perturbed locomotion in bipeds (Geyer et al, 2005;Daley and Biewener, 2006;Seyfarth et al, 2002). We therefore suggest that these parameters play an overall important role during terrestrial locomotion.…”
Section: Discussionmentioning
confidence: 99%
“…During perturbed locomotion, animals instead rely on passive dynamic mechanisms that include spring-mass mechanics and intrinsic mechanisms (see also Biewener and Daley, 2007). In humans and birds, simple spring-mass mechanics mitigate sudden changes in terrain height (Daley and Biewener, 2006;Geyer et al, 2005;Grimmer et al, 2008;Seyfarth et al, 2002). Limbs act as springs and help the system to return to the locomotor trajectory between steps.…”
Section: Introductionmentioning
confidence: 99%
“…The kinematic differences may have resulted from the intrinsic mechanical interaction of the swing leg with the obstacle, resulting in an early transition from swing to stance. Drop perturbations result in similar but inverse dynamics-delayed ground contact leads to a more extended leg posture and shorter stance duration [21].…”
Section: Discussionmentioning
confidence: 99%
“…Animals were trained to run on a level motorized treadmill (Woodway, Waukesha, WI, USA) at speeds of 1.7 -2.0 m s 21 . Training sessions were 20-30 min in duration, with breaks for 1-3 min as needed.…”
Section: Methods (A) Animals and Trainingmentioning
confidence: 99%
“…Such simplifications have allowed discovery of general principles in locomotor modes of walking, running, and climbing (6)(7)(8)(9). Recent studies have generated appreciation for the importance of mechanical interactions with the environment, and through biological experiment (10) and robot modeling (11,12) have demonstrated that stable and robust movement can emerge as a result of appropriately tuned dynamics of limb-ground interaction (13,14). For example, rapid perturbations to locomotion may be corrected by so-called "preflexes" (15) in which mechanical design of the limb and appropriate kinematics enable rapid recovery from perturbation (6,8,10).…”
mentioning
confidence: 99%